2017
DOI: 10.1007/s12029-017-9981-2
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism Is an Independent Predictor of Mortality Among Patients with Gastric Cancer

Abstract: VTE is associated with worse survival among patients with GC along with adenocarcinoma, advanced disease, and PLR. Moreover, these findings were independent of other cancer- and treatment-specific variables. Although potentially predictive in other cancer types, NLR and KRS were not associated with worse survival in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 41 publications
2
28
1
Order By: Relevance
“…In contrast to previous reports, the present study did not show any association between vTEEs and disease outcome or mortality [24,25]. Consistent with our findings are the results from other studies in patients with esophagogastric cancer undergoing preoperative treatment [13,18,20].…”
Section: Discussionsupporting
confidence: 83%
“…In contrast to previous reports, the present study did not show any association between vTEEs and disease outcome or mortality [24,25]. Consistent with our findings are the results from other studies in patients with esophagogastric cancer undergoing preoperative treatment [13,18,20].…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, Shirai et al reviewed 131 patients of pancreatic ductal adenocarcinoma who underwent pancreatic resection and reported perioperative PLR independently predicted disease-free survival and overall survival (10). Fuentes et al reported in their cohort of 112 patients with gastric cancer, that patients stratified as high risk by PLR had worse overall survival (22.6 vs. 42.8 months) (13). In the meta-analysis of patients with colorectal cancer, Huang et al included 17 studies and concluded that elevated PLR was associated with poor overall survival, disease-free survival, as well as higher cancer stage and poor differentiation (7).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the prognostic value of platelet to lymphocyte ratio in patients with hepatocellular carcinoma such as platelet-lymphocyte ratio (PLR), neutrophillymphocyte ratio (NLR), C-reactive protein have been proven as valuable prognostic factors in multiple gastrointestinal cancers including pancreatic ductal adenocarcinoma, colorectal cancer and gastric cancer (7,(9)(10)(11)(13)(14)(15)(16). In HCC however, the results were still conflicting regarding the prognostic value of PLR to predict overall survival and the optimal cut-off of PLR remains unclear (11,(17)(18)(19)(20).…”
Section: Original Articlementioning
confidence: 99%
“…In 2007, Mandala et al 2 demonstrated VTE as a negative prognostic factor for overall and progression-free survival of patients with unresectable pancreatic ductal adenocarcinoma (PDAC). 2 In 2018, Fuentes et al 3 proved VTE as an independent predictor of gastric cancer linked mortality. Like PDAC, gastric cancer is one of the most thrombogenic solid tumors.…”
mentioning
confidence: 99%